Urban Growth Dynamics and Spatial Structure of Major Saudi Cities (Evidence from 2010-2030). - Al-Jarallah, Ahmed Jarallah (International Journal on Humanities & Social Sciences, 2026)
Saudi Arabia has experienced substantial urban transformation during recent decades as a result of rapid demographic growth, economic diversification, and large-scale infrastructure development. This study provides a comprehensive analysis of urban growth patterns in Saudi Arabia between 2010 and 2024 and presents projections of urbanization trends toward 2030. The research employs demographic statistics, comparative analysis of major metropolitan centers, and spatial visualization techniques to examine the dynamics of urban expansion. The findings indicate that the national urbanization rate increased from approximately 82% in 2010 to more than 85% in 2024 and is projected to reach nearly 86-87% by 2030. Major cities including Riyadh, Jeddah, Makkah, Madinah, and Dammam continue to dominate the national urban system and represent the primary centers of economic activity and population concentration. The analysis also highlights the role of Vision 2030 initiatives, infrastructure expansion, and large-scale development projects in shaping the evolving spatial structure of Saudi cities. The study concludes that sustainable urban planning and balanced regional development strategies will be essential for managing continued urban expansion and ensuring long-term urban resilience in the Kingdom.